1985
DOI: 10.1111/j.1360-0443.1985.tb02546.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nicotine Chewing Gum on Smoking Cessation in Routine Clinical Use

Abstract: This is a study ofthe value of adding nicotine chewing gum to group smoking cessation therapy. The results from three periods of such therapy are compared. In periods I and III treatment included group support therapy arui nicotine chewing gum. In period II the group support therapy was identical, but the nicotine replacement chewing gum was, for reasons not provoked by the study, unavailable. The study spans the years 197S-1980 and a total of 2404 smokers. In period I, when the gum was available on a clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…mutans in xylitol-consuming subjects and by BIRKHED et al (9) who found no changes in the salivary numbers of S. mutans and lactobacilli after a 3-month period of frequent xylitol consumption. The reason for the return of 5. mutans to baseline levels after 3 months is not clear but it is not unlikely that bacterial adaptation might have oc- (4-20) 3 1.54 (0.4-3.9) 5.6 (3.13-7.41) 6.0 (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) curred since xylitol-resistant strains of S. mutans have been isolated in high frequency in xylitol consumers (29,30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…mutans in xylitol-consuming subjects and by BIRKHED et al (9) who found no changes in the salivary numbers of S. mutans and lactobacilli after a 3-month period of frequent xylitol consumption. The reason for the return of 5. mutans to baseline levels after 3 months is not clear but it is not unlikely that bacterial adaptation might have oc- (4-20) 3 1.54 (0.4-3.9) 5.6 (3.13-7.41) 6.0 (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) curred since xylitol-resistant strains of S. mutans have been isolated in high frequency in xylitol consumers (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Nicotine-containing cheviing gum is an effec-increase the population of S. mutans in montive adjunct in helping people to quit smok-keys (5) or produce a detectable shift in dening (1)(2)(3) and is used frequently during treat-tal plaque ecology in humans (9). Frequent ment over prolonged periods.…”
mentioning
confidence: 99%
“…With 6-month and 1-year followup on sustainable abstinence rates, most of these studies demonstrate an approximate twofold improvement in cessation rates when the nicotine gum was coupled to other smoking cessation modalities. [140][141][142][143][144][145][146][147][148][149][150][151][152][153][154][155][156][157][158] Attentuation or relief of nicotine withdrawal symptoms have been the main benefit for use of the gum, but the results reported are extremely highly variable. [159][160][161][162][163] Most of these studies assessing the effect of the gum on the nicotine withdrawal complex have been only over relatively very short periods of evaluation.…”
Section: Nicotine Replacement Strategiesmentioning
confidence: 99%